Halal Awareness, Brand Image, and Viral Marketing: Three Key Factors Influencing Purchasing Decisions for Halal Skin Care and Cosmetics Products in Pontianak - Yasir Hudzaifah; Wulan Purnama Sari; Risa Andriyani (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2024)
This research aims to determine the influence of halal awareness, brand image, and viral marketing on the purchasing decisions of halal skincare and cosmetic products (a study on Generation Z in  the environment of Muhammadiyah University Pontianak). The research is conducted within the Muhammadiyah University Pontianak environment. The population of this study includes all students of Muhammadiyah University Pontianak born between the years 1995-2010. The sample for this research consists of 200 students from Muhammadiyah University Pontianak. The data collection technique used is a questionnaire employing a Likert scale. The data analysis technique in this research uses Structural Equation Modeling (SEM) PLS with the SmartPLS Version 3.2.9 program. The results of this research show that halal awareness and brand image do not have a significant influence on purchasing decisions, whereas viral marketing has a positive and significant impact on purchasing decisions for halal skincare and cosmetic products among Generation Z in the Muhammadiyah University Pontianak environment. This study contributes theoretically by exploring the influence of halal product awareness, brand image, and viral marketing variables on purchasing decisions among Generation Z in a university setting. The findings enhance insights into academic literature related to halal skincare and cosmetics, even though halal product awareness and brand image are not significant. Practically, these findings provide guidance for industry practitioners to enhance marketing strategies, especially in the context of viral marketing that has proven to have a positive impact on purchasing decisions. The novelty of the research lies in its focus on Generation Z and the use of the Structural Equation Modeling (SEM) PLS analysis method, contributing to theoretical, practical, and methodological understanding in the context of marketing halal skincare and cosmetic products among Generation Z in a university environment.